The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1029/2022gl098797
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the Western Pacific and Indian Ocean Warm Pools on Wildfires in Yunnan, Southwest China: Spatial Patterns With Interannual and Intraannual Variations

Abstract: The Indo‐Pacific warm pool affects the regional climatic conditions in Southeast Asia mediated by the Western Pacific (WP) and Indian Ocean (IO) monsoons, which are recognized as critical regulators of wildfires in this region. Our study explored the spatiotemporal effects of the warm pools on wildfire records in Yunnan, Southwest China. We showed the interannual records had a negative relationship with the simultaneous WP warm pool area index. The Ailao Mountains in the central Yunnan could be a geographical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…As a result, the extreme drought in Yunnan is a footprint over Southeast Asia. It has been suggested that anthropogenic warming has increased the extreme hot and dry conditions and drought risks over Southwest China (Ma et al 2017, 2021, Luo et al 2022 and even over mainland southeast Asia (Thirumalai et al 2017, Zhang et al 2021). Thus, the extreme winter-spring 2023 drought in Yunnan would have been 'virtually impossible' without human-caused climate change, as suggested by the World Weather Attribution (WWA) to the April heat wave in Southeast Asia (Zachariah et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the extreme drought in Yunnan is a footprint over Southeast Asia. It has been suggested that anthropogenic warming has increased the extreme hot and dry conditions and drought risks over Southwest China (Ma et al 2017, 2021, Luo et al 2022 and even over mainland southeast Asia (Thirumalai et al 2017, Zhang et al 2021). Thus, the extreme winter-spring 2023 drought in Yunnan would have been 'virtually impossible' without human-caused climate change, as suggested by the World Weather Attribution (WWA) to the April heat wave in Southeast Asia (Zachariah et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Yunnan Province in Southwest China is a droughtprone and mountain region, locates in the southeastern margin of the Tibetan Plateau and border with Thailand, Myanmar, Laos and Vietnam. Under recent global warming, Yunnan has witnessed more frequent, severe and longer persistent droughts (Lü et al 2012, Ma et al 2017, 2021, Luo et al 2022, Wang et al 2022. The frequent droughts largely affected the local energy and water supplies, reduced grain production and caused wildfires as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Ying et al. (2022) identified connections between wildfire occurrence in Yunnan, southwest China, and dynamics of the Western Pacific and Indian Ocean warm pools mediated by the regional monsoon climate.…”
Section: Paleofire and Ties To Climatementioning
confidence: 99%
“…From peatland cores in Borneo, Yamamoto et al (2021) inferred at least 12 major fires in the last 6,000 years and tied them to intervals of high solar activity thought to have been associated with drier climate. Finally, Ying et al (2022) identified connections between wildfire occurrence in Yunnan, southwest China, and dynamics of the Western Pacific and Indian Ocean warm pools mediated by the regional monsoon climate.…”
Section: Introductionmentioning
confidence: 99%